The Imagery as a Determinant of Cognitive Adapting - Hovhannisyan, Hrachya (Bulletin of Yerevan University E: Philosophy, Psychology, 2016)
Nowadays, in the new millennium, in the century of the ultra modern technologies, in such conditions of the saturated experimentally psychological data, it is still prevailing the paradigm of the passivity of perception and image. The image is still treated as a representation, as a secondary phenomenon, a performance. The process of formation of the subjective image is still viewed as a modeling of objective reality. We always bother ourselves with thoughts and questions about what lies beyond our senses, visualizing the reality outside of the subject. The facts about the "external (material) world", which are interpreted as a transcendental personality, or objectively mediated ones are the products of the imagery quality. What we call the object of sensations or reality outside of the subject, actually are our understanding and knowledge of the transcendent. Images of the latter and are attributed by us to the physical world. This attribution is almost identical to one of the characteristics of perception: objectivity, as the possibility of projection of the inner world to the outside world. We call this phenomenon "Externalization of mental images". Here we especially highlight the deterministic focus of mental activity "From the inside to outside", where the subject as if making a process of recreating the reality. From our point of view of the ecological attitude that is a cognitive adaptation to the subject (with its subsystems) to the informative environment. In our opinion, as a result of this adaptation process, the imagery is set as the main backbone factor of the experience of reality comprehension. We believe that cognitive adaptive dynamics is a manifestation of the closest connection (contact) of the subject to the surrounding world. And the cognitive experience with trainings must be also considered in terms of adaptation. There is a good chance that this cognitive experience (most likely the skill) comes from the quality of imagery. The effectiveness of cognitive adaptation and is an indicator of experience. But the imagery is that ability, on the basis of which occur in the process of cognition phenomenon of reality.